2003
DOI: 10.1039/b304809h
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring priority substances of directives 76/464/EEC and 2000/60/EC in Greek water bodies

Abstract: The priority substances of List I, 76/464/EEC Directive, some of which belong to the new Water Framework Directive 2000/60/EC, have been monitored in the surface waters of Greece through the developed network of 53 sampling stations. The analytical methods used for the determination of these substances included Purge and Trap-Gas chromatography-Mass spectrometry for volatile and semivolatile organic compounds, Gas Chromatography-Electron Capture Detection for organochlorine insecticides, High Performance Liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
0
2
0
4
Order By: Relevance
“…In previous monitoring studies, Golfinopoulos et al (2003) found several organochlorine pesticides but not lindane whereas Lekkas et al (2003) were able to detect hexachlorocyclohexane, aldrin, endrin and dieldrin. Lekkas et al (2004) reported the detection of organophosphorus insecticides, triazine (including prometryn) and phenylurea (not fluometuron) herbicides.…”
Section: Lake Vistonismentioning
confidence: 95%
“…In previous monitoring studies, Golfinopoulos et al (2003) found several organochlorine pesticides but not lindane whereas Lekkas et al (2003) were able to detect hexachlorocyclohexane, aldrin, endrin and dieldrin. Lekkas et al (2004) reported the detection of organophosphorus insecticides, triazine (including prometryn) and phenylurea (not fluometuron) herbicides.…”
Section: Lake Vistonismentioning
confidence: 95%
“…Conventional methods, such as LLE , require the use of large amount of expensive high‐purity organic solvents, which are often hazardous, and is laborious, time‐consuming, and apt to form emulsions. To avoid these drawbacks, several environmentally friendly sample pretreatment techniques, including purge and trap (P&T) , direct aqueous injection (DAI) , SPME , LPME , static headspace (static HS) , headspace solid‐phase dynamic extraction (HS‐SPDE) , headspace solid‐phase microextraction (HS‐SPME) , static headspace knotted hollow fiber microextraction (HS‐K‐HPME) , headspace single drop microextraction (HS‐SDME) , and headspace liquid‐phase microextraction (HS‐LPME) , have been arisen. P&T is the pre‐concentration method for VCHCs from water most frequently used in routine analysis in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Η συμβολή των οργανοχλωριωμένων φυτοπροστατευτικών προϊόντων στην αύξηση της γεωρ γικής παραγωγής ήταν ιδιαίτερα καθοριστική. Αποτέλεσμα της εκτεταμένης χρήσης αυτών είναι η ανίχνευση υπολειμματικών συγκεντρώσεων τους σε επιφανειακά και υπόγεια νερά, στο έδαφος, σε στελέχη φυτών, σε ανώτερους θαλάσσιους οργανισμούς, σε πουλιά, σε ερπετά, σε θηλαστικά και τέ λος στον ίδιο τον άνθρωπο (Karadanelli et al, 1998;Golfinopoulos et al, 2003;Hernâdez et al, 2000;Ribeiro et al, 2005).…”
Section: ιστορικη αναδρομηunclassified